Preparation of Three-dimensional (3-D) Human Liver (HepaRG) Cultures for Histochemical and Immunohistochemical Staining and Light Microscopic Evaluation. (August 2018) - Clayton, Natasha P.; Burwell, Alanna; Jensen, Heather; Williams, Barbara F.; Brown, Quashana D.; Ovwigho, Pamela; Ramaiahgari, Sreenivasa; Hermon, Tonia; Dixon, Darlene
The use of three-dimensional (3-D) in vitro culture systems (spheroids, organoids) in biomolecular and drug discovery research has become increasingly popular. The popularity is due, in part, to a diminished reliance on animal bioassays and a desire to develop physiologically relevant cell culture systems that simulate the in vivo tissue microenvironment. Most evaluations of 3-D cultures are by confocal microscopy and high-content imaging; however, these technologies do not allow for detailed cellular morphologic assessments or permit basic hematoxylin and eosin histologic evaluations. There are few studies that have reported detailed processes for preparing 3-D cultures for paraffin embedding and subsequent use for histochemical or immunohistochemical staining. In an attempt to do so, we have developed a protocol to paraffin-embed human liver spheroids that can be sectioned with a microtome and mounted onto glass slides for routine histochemical and immunohistochemical staining and light microscopic evaluations.